Kierkegaard and a Religionless Christianity - Kirkpatrick, MD (2008)
The central aim of this thesis is to analyse the influence of Kierkegaard on Bonhoeffer. This relationship has been almost universally recognized. And yet this area has received no comprehensive study, limited within the secondary literature to footnotes, digressions, and the occasional paper. Furthermore, what little literature there is has been plagued by several stereotypes. First, discussion is often limited to Discipleship. Second, Kierkegaard has been identified as an individualist and acosmist who rejected the church, leading many to consider Bonhoeffer the ecumenist and ecclesiologist as selectively agreeing with Kierkegaard, but ultimately rejecting his overall stance. This thesis will argue that neither stereotype is true, and suggest (a), that Kierkegaard’s influence can be found throughout Bonhoeffer’s work, and (b) that although a more stereotypical perspective may be present in SC, by the end of his life Bonhoeffer had gained a far deeper understanding across the breadth of Kierkegaard’s work. The importance of this thesis is not simply to ‘plug the gap’ of scholarship in this area, but also to suggest the importance of analysing Kierkegaard and Bonhoeffer together. This will focus on three specific areas. First, alongside the influence of Kierkegaard on Bonhoeffer, it will argue for the importance of using Bonhoeffer as an interpretive tool for understanding Kierkegaard. This thesis will show how Bonhoeffer adopted and adapted Kierkegaard’s work to his own situation, forcing Kierkegaard to answer questions that were not present during his own life. In this way, we are led to compare Kierkegaard and Bonhoeffer as individuals, and not simply their static declarations. Secondly, against the tendency to consider Kierkegaard and Bonhoeffer’s final attacks on Christendom as unfortunate endings to otherwise profound careers, it will be suggested that these attacks stand as the fulfilment of their earlier thought. It will be argued that despite their different contexts, both Kierkegaard and Bonhoeffer were led to the same conclusions concerning Christendom. Thirdly, given Kierkegaard’s submission to indirect communication and his somewhat 'prophetic' proclamations concerning one who will come after him and reform, this thesis will ask whether Bonhoeffer stands as something of a fulfilment to Kierkegaard’s thought in the guise of a Kierkegaardian ‘reformer’.